Boundary feedback stabilization of hydraulic jumps. (30th March 2019) - Bastin, Georges; Coron, Jean-Michel; Hayat, Amaury; Shang, Peipei
Abstract: In an open channel, a hydraulic jump is an abrupt transition between a torrential (supercritical) flow and a fluvial (subcritical) flow. In this article hydraulic jumps are represented by discontinuous shock solutions of hyperbolic Saint-Venant equations. Using a Lyapunov approach, we prove that we can stabilize the state of the system in H 2 -norm as well as the hydraulic jump location, with simple feedback boundary controls and an arbitrary decay rate, by appropriately choosing the gains of the feedback boundary controls.